Endovascular Repair of an Isolated Iliac Artery Aneurysm in a Patient with Liver Cirrhosis - Azadeh Tahooni; Milad Vahedinezhad (International Journal of Cardiovascular Practice, 2019)
Endovascular repair is increasingly becoming the main strategy for management of aortic and peripheral aneurysms. Several methods have been introduced to treat aneurysms based on anatomy, coexisting nearby aneurysms and available tools. We presented a 60-year-old man with an isolated large iliac artery aneurysm found incidentally treated using an endovascular approach and obliterating internal iliac artery without early and late complications at 3-year follow-up.